2022
DOI: 10.1042/bcj20220388
|View full text |Cite
|
Sign up to set email alerts
|

TOR complex 2 is a master regulator of plasma membrane homeostasis

Abstract: As first demonstrated in budding yeast (Saccharomyces cerevisiae), all eukaryotic cells contain two, distinct multi-component protein kinase complexes that each harbor the TOR (Target Of Rapamycin) polypeptide as the catalytic subunit. These ensembles, dubbed TORC1 and TORC2, function as universal, centrally important sensors, integrators, and controllers of eukaryotic cell growth and homeostasis. TORC1, activated on the cytosolic surface of the lysosome (or, in yeast, on the cytosolic surface of the vacuole),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 235 publications
1
28
0
Order By: Relevance
“…In S. cerevisiae, TOR-Ypk1 also regulates the function of phospholipid flippases responsible for maintaining the asymmetric distribution of PS and PE at the plasma membrane (30,36). Our data suggests that the TOR-Ypk1 axis functions differently in C. neoformans compared to S. cerevisiae.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In S. cerevisiae, TOR-Ypk1 also regulates the function of phospholipid flippases responsible for maintaining the asymmetric distribution of PS and PE at the plasma membrane (30,36). Our data suggests that the TOR-Ypk1 axis functions differently in C. neoformans compared to S. cerevisiae.…”
Section: Discussionmentioning
confidence: 81%
“…Our work has shed light on the role of the TOR pathway in maintaining lipid homeostasis at host CO2 concentrations in C. neoformans. Previous studies in S. cerevisiae (36) as well as in C. neoformans (37) have shown that TOR acts through its target Ypk1 to regulate both phospholipid asymmetry at the plasma membrane and sphingolipid biosynthesis. The ypk1∆ mutant is highly sensitive to CO2, indicating that this arm of the TOR pathway is also critical to high CO2 adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…As reduced LPD-3 activity results in impaired ER-to-PM phospholipid trafficking, a lipid homeostatic mechanism is likely triggered to up-regulate sphingolipids in lpd-3 mutants. 26 Given reported sphingolipid modulation of mTOR signaling and longevity, 41 43 we next explored the link of hexaceramide biosynthetic enzyme HYL-1 to ins-7 . We found that hyl-1 RNAi led to a strong suppression of ins-7 p∷INS-7∷GFP in lpd-3 mutants ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…When these are flattened, the associated TORC effectors Slm1 and Slm2 are released and TORC2 is activated, which operates as a master regulator of membrane and wall-related processes [152]. TORC2 controls membrane and protein homeostasis [144,153], including the synthesis of sphingolipids and cytoskeleton reorga-nization which is also indispensable for polarization and invasion, as well as differentiation into pseudo or true hyphae. But maybe more important is that TORC2 and the ESCRT complex [154] are functionally related in the dependence of calcineurin [155].…”
Section: Candida Famatamentioning
confidence: 99%